Banana Fibers as Sorbent for Removal of Acid Green Dye from Water - Siti Kartina Abdul Karim; Soh Fong Lim; S. N. David Chua; Shanti Faridah Salleh; Puong Ling Law (Journal of Chemistry)
In this study, banana fibers extracted from banana leaves, stem, and stalk were used to remove acid green dye from aqueous solution. Three initial concentrations (750, 1000, and 1500 ppm) were chosen to determine the kinetic characteristics of the banana fiber sorbents at 25°C, agitation speed of 200 rpm, and total contact time of 3 hours. The pseudo-first-order, pseudo-second-order, and Dunwald-Wagner kinetic models were applied to the experimental kinetic data. For isotherm study, the batch experiments were performed at 25°C, initial pH 2, agitation speed of 200 rpm, and initial concentrations between 100 and 2000 ppm. The experimental data was fitted to the Langmuir, Freundlich, Dubinin-Radushkevich, and Temkin isotherms. The equilibrium was achieved in less than 90 minutes. The removal of the acid green dye was found to be following closely the pseudo-second-order kinetic model. For equilibrium study, the Freundlich isotherm was found to fit well with adsorption of acid green dye on the banana leaves, stem, and stalk sorbents. The calculated mean free energy of 4–11 J/mol indicated that the sorption process was mostly physical in nature. Experimental results also showed the adsorption performance is greatly affected by the initial solution pH.